Boosting photocatalytic overall water splitting by Co doping into Mn3O4 nanoparticles as oxygen evolution cocatalysts. Issue 22 (4th April 2018) - Yoshinaga, Taizo; Saruyama, Masaki; Xiong, Anke; Ham, Yeilin; Kuang, Yongbo; Niishiro, Ryo; Akiyama, Seiji; Sakamoto, Masanori; Hisatomi, Takashi; Domen, Kazunari; Teranishi, Toshiharu
Abstract : Cobalt doping into a Mn3 O4 nanoparticle cocatalyst enhanced photocatalytic water splitting activity of a Mn3 O4 cocatalyst/photocatalyst system. Abstract : The effect of cobalt doping into a manganese oxide (tetragonal spinel Mn3 O4 ) nanoparticle cocatalyst up to Co/(Co + Mn) = 0.4 (mol/mol) on the activity of photocatalytic water oxidation was studied. Monodisperse ∼10 nm Co y Mn1− y O (0 ≤ y ≤ 0.4) nanoparticles were uniformly loaded onto photocatalysts and converted to Co x Mn3− x O4 nanoparticles through calcination. 40 mol% cobalt-doped Mn3 O4 nanoparticle-loaded Rh@Cr2 O3 /SrTiO3 photocatalyst exhibited 1.8 times-higher overall water splitting activity than that with pure Mn3 O4 nanoparticles. Investigation on the band structure and electrocatalytic water oxidation activity of Co x Mn3− x O4 nanoparticles revealed that the Co doping mainly contributes to the improvement of water oxidation kinetics on the surface of the cocatalyst nanoparticles.